The impact of Kangaroo Mother Care (KMC) video as the counseling media towards the impro ement of pregnant mother knowledge in Kubu Raya Regency of West Borneo in 2018 - Dwi Khalisa Putri; Daevi Khairunisa (International Journal of Health Science and Technology, 2020)
Weight is one of the health indicators on new born babies. New born babies have issuesbecause they are in the transition phase from intrauterine to extra uterine. The provision of information through audiovisual media will be more practical and flexible for the community in improving knowledge. The health counseling media are one of the components of learning process. Video is one of the media which presents information or message in an audiovisual manner. The aim of the research wasto identify the impact of KMC video as a counseling media on the improvement of mothers’ knowledge regarding baby management with Low Birth Weight. Method: This research applied experimental method with quasi experiment design through time series. The research samples were 36 pregnant mothers who lived in facilitated area of Punggur Kecil in Sui Kakap District of Kubu Raya Regency through Purposive Sampling as the sample determination technique. The data analyses employed paired t-test and one sample t-test. There was an improvement from the previous value before and after the counseling with 67,5% (p0,05) of rate. The KMC video as the counseling media hada significant impact (p0,05) towards the improvement of knowledge. The application of KMC video as the counseling media had impact on the improvement of mothers’ knowledge regarding baby management with Low Birth Weight.